The Impact of Social-Economic-Status on EFL Learners’ Foreign Language Anxiety in Language Classrooms in Afghanistan - Zia, Ziaurahman; Safi, Mohammad Dost (International Journal For Research In Educational Studies, 2020)
Studies conducted on language anxiety have found that foreign language anxiety (FLA) is an affecting variable in language learning. There is a negative correlation between foreign language anxiety and learners achievements (Aida, 1994; and Horwitz, 2001). This study aims to examine English as foreign language learners’ FLA in language classrooms. It also investigates the impact of SES onlearners' foreign language anxiety inside language classroom. The participants of the study are 100 first year EFL undergraduates from Nangarhar University in Afghanistan. The adapted version of (Horwitz, et al., 1986) Foreign Language Classroom Anxiety Scale (FLCAS) is used for data collection in the study.The results suggested that learners’ suffer from high level of FLA. It revealed that learners with lower socio-economic background experienced higher levels of FLA in their foreign language classrooms. learners from low-income backgrounds usually attend schools with lower funding levels and this situation reduced learners’ motivation which affects their LL and achievements inside and outside of the classroom.